2012
DOI: 10.1111/j.1447-0756.2012.01872.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic and hysteroscopic outcomes of uterine scar healing after cesarean section: Comparison of two types of single‐layer suture

Abstract: Aim:  A common anatomical consequence of low‐segment cesarean section is the presence of a pouch on the anterior uterine wall that can be detected by sonography or hysteroscopy. Different suturing techniques have been compared (single vs double layer) and showed no substantial differences. This prospective longitudinal study was aimed at evaluating the outcome of the cesarean scar, comparing two different types of single‐layer sutures by transvaginal ultrasound and hysteroscopy. Material and Methods:  The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…Because of that, the risk of severe obstetric complications, such as uterine rupture, subsequent hemorrhage or morbidly adherent placenta, is still very high, regardless of the present therapeutic achievements [11, 15, 3840]. The exact reasons for scar defects after cesarean sections still remain unknown [41, 42]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of that, the risk of severe obstetric complications, such as uterine rupture, subsequent hemorrhage or morbidly adherent placenta, is still very high, regardless of the present therapeutic achievements [11, 15, 3840]. The exact reasons for scar defects after cesarean sections still remain unknown [41, 42]. …”
Section: Discussionmentioning
confidence: 99%
“…It might also be a treatment option (depending on the center) [5, 9, 14, 34, 41, 4345]. In the ultrasound, the isthmocele appears as a hypoechoic triangular area in the previous hysterotomy place.…”
Section: Discussionmentioning
confidence: 99%
“…One RCT and a prospective longitudinal study compared locked to unlocked sutures (Yasmin et al, 2011;Ceci et al, 2012). Yasmin et al showed decreased myometrial thickness (60 patients; mean difference, 22.5; 95% CI, 23.2 to 21.8; P , 0.001) and increased blood loss (60 patients; mean difference, 45.0 ml; 95% CI, 21.6 -68.4; P , 0.001) with locking of the first layer.…”
Section: Hypothesis 2: Incomplete Closure Of the Uterine Wallmentioning
confidence: 99%
“…The niche is visible during the examination as a triangular hypoechogenic area, with its apex directed towards the anterior wall of the uterine isthmus, whereas the base is directed towards its posterior wall. Other methods used in “isthmocele” diagnostics are endoscopic techniques (mainly hysteroscopy) [10, 13, 18, 23, 27, 28, 32, 33]. …”
Section: Discussionmentioning
confidence: 99%